Regulation and status of herbal medicine clinical trials in Korea - Boram Lee; Yujin Choi; Pyung-Wha Kim; Changsop Yang; Myeong Soo Lee (Integrative Medicine Research)
Background: Herbal medicine has been used frequently in Korean medicine. We aimed to summarize the relevant regulations for herbal medicine clinical trials and to analyze their current status in the Republic of Korea. Methods: We searched for legislation to find regulations on herbal medicine clinical trials. Additionally, the websites of the Korean Ministry of Food and Drug Safety (KMFDS) and Clinical Research Information Service (CRIS) were searched to investigate the current status of them. Results: To conduct herbal medicine clinical trials for new drugs or previously approved drugs outside of indications, investigational new drug (IND) approval should be obtained from the KMFDS. For clinical trials of herbal medicines that have been used for more than 3 years with 200 cases at the clinical trial institution, nonclinical data can be exempted from IND approval. Total 95 and 108 herbal medicine clinical trials from the KMFDS and CRIS websites were analyzed. The number of clinical trials showed an increasing trend each year, as did KMFDS-regulated clinical trials. Recently, three clinical trials targeting new herbal formulations frequently used in Korean medicine institutions have been approved based on relevant regulations. Conclusion: We confirmed that herbal medicine clinical trials are managed through strict regulations, which can ensure the safe and effective use of herbal medicine. Despite strict regulations, attempts to accumulate evidence through clinical trials for herbal medicine are increasing. High-quality clinical trials should be conducted to develop new drugs that reflect the clinical setting using relevant regulations, evaluate the efficacy and safety of the drugs, and strengthen insurance coverage.